1994
DOI: 10.1007/bf01719291
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of hepatitis B virus infection in Greek patients with various types of glomerulonephritis

Abstract: The frequency of hepatitis B surface antigen (HBsAg) was studied in the sera of 622 patients with glomerulonephritis (GN). The prevalence of HBs-antigenemia was 2.8% (18/622; eleven adults and seven children); the difference from 2.6% in the general population of Central and Southern Greece was not statistically significant (chi 2 = 0.01; p > 0.50). Two of the 11 HBsAg-seropositive adult patients with GN suffered from IgA nephropathy, one from IgA and membranous glomerulonephritis (MGN), four from diffuse prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Although the etiological role and association analysis of HBV in IgAN have been continuously studied, some conclusions are controversial. 6 , 7 Some early clinical studies suggested that hepatitis B did not play a role in the pathogenesis of IgAN, 8 , 9 or even did not affect the prognosis of IgAN. 10 However, some recent retrospective studies suggested clinicopathological differences between hepatitis B surface antigen (HBsAg)-positive IgAN and primary IgAN without HBV infection.…”
mentioning
confidence: 99%
“…Although the etiological role and association analysis of HBV in IgAN have been continuously studied, some conclusions are controversial. 6 , 7 Some early clinical studies suggested that hepatitis B did not play a role in the pathogenesis of IgAN, 8 , 9 or even did not affect the prognosis of IgAN. 10 However, some recent retrospective studies suggested clinicopathological differences between hepatitis B surface antigen (HBsAg)-positive IgAN and primary IgAN without HBV infection.…”
mentioning
confidence: 99%